The foreign gaze on the trip from Rio de Janeiro to Morro Velho: nature, enslaved, freedmen and immigrants in Richard F. Burton's reports about Brazil (1869) (Ágora Journal, 2022)
The English diplomat Richard F. Burton published the book Viagem do Rio de Janeiro a Morro Velho (1869), a report of his passage through Minas Gerais from an exercise of selection and creativity linked to the formulation of an idea of Brazil for the European world. By mobilizing travel literature as a support that expresses senses and meanings to the social world, we connect the theoretical and methodological issues that govern the objective of this article, to analyze Richard Burton’s travel descriptions of the Brazilian population, from the problematization of the character. Based on geographic determinism and racist principles, Burton highlighted the demographic imbalance of the country, based on Eurocentrism and on the perspective of Brazil’s lag caused by “mestizaje”, reinforcing the argument that the solution would be the implementation of immigration policies directed to Europeans as a strategy for the “civilization” of the Brazilian population.